Sqrt 363 - 3 sqrt27
= sqrt(121* 3) - 3 sqrt (9*3)
= sqrt 121* sqrt3 - 3 * sqrt 9 * sqrt3
= 11 sqrt3 - 3* 3 sqrt3
= 11 sqrt3 - 9 sqrt3
= 2 sqrt3 Answer
Answer: y = 7
Explanation:
7^8/7y = 7^6
7^7/y = 7^6
In order for 7^7 to become 7^6 you need to divide by 7
Which mean y = 7
So that:
7^7/7= 7^6
7^6 = 7^6
-2x^2 + 3x - 9 = 0
The quadratic is not factorable so quadratic formula must be used.
x = (-b + - √(b^2 - 4ac))/2a
a = -2, b = 3, c = -9
x = (-3 + - √(9 - 4*-2*-9))/-4
x = (-3 + - √(-63))/-4
x = -3 + - 3i√7
--------------
-4
x = 3 + 3i√7 x = 3 - 3i√7
------------ ------------
4 4
Answer:
scale factor is 169
Step-by-step explanation: